Alternative Strategy to Increase Room Sales at Pramana Watu Kurung - Budiasa, Kadek; Ernawati, Ni Made; Triyuni, Ni Nyoman (Jurnal Sains Terapan Pariwisata, 2024)
Purpose: The Pramana Watu Kurung is a local chain hotel under Pramana Hotels & Resorts. The promotional strategy online as well as offline to increase room sales. Data shows to see the revenue growth from 2018 to 2019 however, it is fall in 2020 due to the pandemic Covid-19, there was massive cancellation and drop the revenue due to Bali was start to lock down in March 2020. This study is aim to know the strategy applied to increase Room Sales at Pramana Watu Kurung in facing competition and developing business growth and to find alternative strategy to increase room sales at Pramana Watu Kurung.Methods: This study is quantitative and qualitative with the questionnaire on the likert scale. Its method uses SWOT analysis on IFAS and EFAS.Implication: Second  strategies to maximize the strengths in order to eliminate threats which is apply dynamic pricing tobe competitive against the competition and focus on the current target market. Second strategy is to maximize the opportunities to eliminate the weaknesses by an attractive promotion including packages, email marketing and seasonal campaign to push room sales.